2013
DOI: 10.1242/jcs.118992
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling via Akt2 switches plakophilin 1 functions from stabilizing cell adhesion to promoting cell proliferation

Abstract: SummaryDownregulation of adherens junction proteins is a frequent event in carcinogenesis. How desmosomal proteins contribute to tumor formation by regulating the balance between adhesion and proliferation is not well understood. The desmosomal protein plakophilin 1 can increase intercellular adhesion by recruiting desmosomal proteins to the plasma membrane or stimulate proliferation by enhancing translation rates. Here, we show that these dual functions of plakophilin 1 are regulated by growth factor signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 79 publications
1
44
0
Order By: Relevance
“…8). Others have previously shown that exogenous expression of plakophilin isoforms can increase intercellular adhesion (Roberts et al, 2013;Setzer et al, 2004;Wolf et al, 2013). By contrast, expression of the Myc-tagged plakophilin palmitoylation mutants failed to increase intercellular adhesion in these cultures.…”
Section: Expression Of Mutant Plakophilins Disrupts Cell-cell Adhesionmentioning
confidence: 85%
“…8). Others have previously shown that exogenous expression of plakophilin isoforms can increase intercellular adhesion (Roberts et al, 2013;Setzer et al, 2004;Wolf et al, 2013). By contrast, expression of the Myc-tagged plakophilin palmitoylation mutants failed to increase intercellular adhesion in these cultures.…”
Section: Expression Of Mutant Plakophilins Disrupts Cell-cell Adhesionmentioning
confidence: 85%
“…For instance, Dp either supports (Gallicano et al 1998) or inhibits proliferation depending on cell type, the latter through suppression of Erk and Akt (Wan et al 2007). In turn, growth factor signaling can convert desmosomal components from adhesive to pro-proliferative functions as in the case of insulin signaling via Akt2 causing Pkp1 to promote proliferation and migration (Wolf et al 2013). Collectively, these observations suggest that the core building blocks of desmosomes are tailored to support specific functions within complex tissues and are important for controlling epidermal homeostasis.…”
Section: Roles For Desmosome Molecules In Morphogenesis and Homeostasmentioning
confidence: 99%
“…A recent report shows how phosphorylation of PKP1 controls the distribution between its desmosomal and cytoplasmic pools and shifts the balance from an adhesion promoting function of un-phosphorylated PKP1 to a translation and proliferation promoting function of the phosphorylated form (Figure 4, [Wolf et al, 2013]). Insulin/IGF-1-signaling via the PI3K -AKT pathway induced the phosphorylation of the PKP1 head domain.…”
Section: Regulation Of Multifunctional Pkps By Phosphorylationmentioning
confidence: 99%